2015
DOI: 10.14392/asaa.2015080206
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres No Topo: As Contadoras Paranaenses Estão Rompendo O Glass Ceiling?

Abstract: Resumo: Ao longo das últimas décadas um número crescente de mulheres tem se formado em Ciências Contábeis no Brasil. No entanto, a sub-representação das mulheres na Contabilidade simplesmente evoluiu da segregação horizontal, rejeição das mulheres da profissão, para uma segregação vertical, em que as mulheres encontram dificuldades de alcançar altos cargos gerenciais dentro das organizações (DAMBRIN; LAMBERT, 2008). No entanto, Altman e Simpson (2000) sugerem que essas barreiras podem ser perfuradas por mulher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(37 reference statements)
0
2
0
8
Order By: Relevance
“…They found that the glass ceiling and work-life balance conflicts have been responsible for the creation of barriers that hinder the advancement of women throughout the accountant career. Souza, Voese and Abbas (2015) found that the young female accountants are breaking the glass ceiling in the search for progress in accounting career. In order to explore this proposition, they carried out a comparative analysis among young and mature female accountants.…”
Section: Glass Ceiling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the glass ceiling and work-life balance conflicts have been responsible for the creation of barriers that hinder the advancement of women throughout the accountant career. Souza, Voese and Abbas (2015) found that the young female accountants are breaking the glass ceiling in the search for progress in accounting career. In order to explore this proposition, they carried out a comparative analysis among young and mature female accountants.…”
Section: Glass Ceiling Approachmentioning
confidence: 99%
“…Regarding the study by Brighenti, Jacomossi and Silva (2015) this research extends the vision of gender inequality, not only focused on salary issues, but entering the invisible barriers that prevent women to join the most prestigious careers in the accounting profession. Regarding the study by Sousa, Voese and Abbas (2015), the differential has been assessing gender inequality by the employment of women in the accounting profession at different hierarchical levels contributing to the theoretical and empirical field on the effectiveness of glass ceiling.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos evidentes avanços, em se tratando de diferenças salariais e da ocupação de cargos mais valorizados, ainda persiste a histórica dominação masculina na área contábil, com pouca atuação de contadoras nos cargos da alta hierarquia, ratificando as desigualdades de gênero no mercado de trabalho (GAMMIE; GAMMIE; MATSON; DUNCAN, 2007, RAMDHONY;OOGARAH-HANUMAN;SOMIR, 2013;ALTOÉ, 2014) e a divisão sexual do trabalho. Percebe-se, dessa forma, uma substituição do que foi considerado anteriormente uma significativa desigualdade de gênero, que estabelecia a rejeição das mulheres na área, pelo denominado efeito glass ceiling, que em tradução livre para o português significa teto de vidro, e diz respeito ao fenômeno social que representa as barreiras e dificuldades enfrentadas pelas mulheres para ascenderem profissionalmente (DAMBRIN; LAMBERT, 2008;VOESE;ABBAS, 2015;BERTRAND;BLACK;JENSEN;LLERAS-MUNEY, 2019).…”
Section: Introductionunclassified
“…O fenômeno é estudado em relação às mulheres executivas brasileiras (MOTA SANTOS; TANURE; CARVALHO NETO 2014; CARVALHO NETO; TANURE; MOTA-SANTOS, 2014;LIMA et al, 2013) independente da função e, também, na área contábil (SOUZA; VOESE; ABBAS, 2015;DAL MAGRO, SILVA, 2016). Além do teto de vidro, existe outra terminologia que define os obstáculos que podem impedir o acesso de mulheres a certos departamentos.…”
Section: Introductionunclassified